2015
DOI: 10.1038/ncb3253
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian pexophagy target

Abstract: Protein ubiquitination in mammals is known to trigger selective autophagy of peroxisomes, through a process termed pexophagy. Until now, the peroxisomal target for pexophagy-related ubiquitination was controversial, but two studies have identified the protein PEX5 as the real candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Several questions remain to be addressed, however, and it will be interesting to compare differences in the mechanisms that regulate clearance of different organelles, such as peroxisomes and mitochondria. For example, how does the ubiquitination of PEX5 lead to pexophagy, as various residues can be ubiquitinated on PEX5 leading to different fates (Subramani, 2015). Also, though PMP70 is ubiquitinated by PEX2 during amino acid depletion conditions, it is unclear whether ubiquitination of PMP70 alone induces pexophagy.…”
Section: Selective Autophagy Of Organellesmentioning
confidence: 99%
“…Several questions remain to be addressed, however, and it will be interesting to compare differences in the mechanisms that regulate clearance of different organelles, such as peroxisomes and mitochondria. For example, how does the ubiquitination of PEX5 lead to pexophagy, as various residues can be ubiquitinated on PEX5 leading to different fates (Subramani, 2015). Also, though PMP70 is ubiquitinated by PEX2 during amino acid depletion conditions, it is unclear whether ubiquitination of PMP70 alone induces pexophagy.…”
Section: Selective Autophagy Of Organellesmentioning
confidence: 99%
“…Another common organellophagy is pexophagy, a type of autophagy that participates in the quality control of peroxisomes, which is important to lipid metabolism and hydrogen peroxide production and degradation (Nordgren et al 2013). Several proteins that are involved in peroxisome biogenesis, e.g., peroxins (encoded by PEX genes), including Pex3, Pex5 and Pex14, are suggested to participate in macropexophagy (Sakai et al 2006; Manjithaya et al 2010; Neuhaus et al 2014; Subramani 2015). An oncoprotein, hypoxia inducible factor 2α (HIF2α), has also been indicated to induce hepatocyte pexophagy (Walter et al 2014).…”
Section: Autophagy: the Basic Processmentioning
confidence: 99%
“…As of now, most of the gathered data refers to ubiquitin-dependent pexophagy and point to ubiquitin as a factor in triggering pexophagy. Although work from two groups has identified PEX5 as a putative physiological target for ROS-induced pexophagy, it is unclear how exactly this works because other sites for ubiquitylation on PEX5 have been described, each leading to different physiological fates [111]. These details remain to be sorted out.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…These ubiquitin-binding proteins may not be a sufficient mechanism for all physiological forms of pexophagy [111]. It was recently shown that down-regulation of PEX14 partly protects peroxisomes from NBR1-induced pexophagy [54].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation